2017
DOI: 10.1542/hpeds.2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pediatric Rapid Response Team Performance Through Crew Resource Management Training of Team Leaders

Abstract: Targeted crew resource management training of the team leader resulted in improved team performance and dynamics for patients requiring transfer to the ICU. The intervention demonstrated that training the team leader improved behavior in RRT members who were not trained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…In the airline industry, standardized communication protocols have almost eliminated adverse events as a result of human error [13]. Attempts to implement some of these strategies in the medical field were previously attempted [21,22]. Leading healthcare authorities, including the Agency for Healthcare Research and Quality and the Department of Defence, recognized the importance of team training and communication and have invested significant resources in developing 'Team Strategies and Tools to Enhance Performance and Patient Safety' (TeamSTEPPS).…”
Section: Discussionmentioning
confidence: 99%
“…In the airline industry, standardized communication protocols have almost eliminated adverse events as a result of human error [13]. Attempts to implement some of these strategies in the medical field were previously attempted [21,22]. Leading healthcare authorities, including the Agency for Healthcare Research and Quality and the Department of Defence, recognized the importance of team training and communication and have invested significant resources in developing 'Team Strategies and Tools to Enhance Performance and Patient Safety' (TeamSTEPPS).…”
Section: Discussionmentioning
confidence: 99%
“…There was a particular focus on leadership skills training which improved overall NTS ratings, consistent with the required role of the team leader to orchestrate the team's activities. 11,30 This clearly indicates that leadership and teamwork skills can be developed and perhaps debunks the argument that leaders are born rather than made. 37 Training impact was demonstrated at Levels 1-3 on Kirkpatrick's hierarchy but with no outcomes at Level 4.…”
Section: Discussionmentioning
confidence: 97%
“…Mahramus et al 26 found that interprofessional emergency teams' global scores improved significantly after simulation training (P < 0.001), and we computed a large effect of training (Cohen's d = 1.10). Similarly, Siems et al 30 who assessed paediatric rapid response teams after team leader crew resource management training, found global scores improved from M = 6.0 to M = 9.0 (M = 90%, P = <0.001) but final TEAM total mean scores of 79.5% in intervention and control groups did not differ. Interprofessional training of student medical/nursing teams reported by Morse et al 27 These comparisons verify that NTS teamwork performance can be enhanced by practice.…”
Section: Validity Evidence Of Training Outcomesmentioning
confidence: 90%
See 1 more Smart Citation
“…Most research that has applied teamwork training in pediatric patients also evaluated the fulfillment and awareness of participants after instructions, recording positive feedback, mainly on reliance, knowledge, and skills to proceed with CPR. 8,[16][17][18][19][20]22,25,39,40 A controlled and randomized study assessed the effect of teamwork training on cooperation and coordination among professionals using the TeamSTEPPS Essentials model in the PALS course of AHA. 41 This methodology is almost identical to ours and obtained significantly higher awareness of teamwork, cooperation, knowledge of the situation, and abilities to assist in teams' decision-making.…”
Section: Found An Increase Inmentioning
confidence: 99%